Food safety concerns deriving from the use of silver based food packaging materials - Pezzuto, Alessandra; Losasso, Carmen; Mancin, Marzia; Gallocchio, Federica; Piovesana, Alessia; Binato, Giovanni; Gallina, Albino; Marangon, Alberto; Mioni, Renzo; Favretti, Michela; Ricci, Antonia (Frontiers in Microbiology, 2015)
The formulation of innovative packaging solutions, exerting a functional antimicrobial role in slowing down food spoilage, is expected to have a significant impact on the food industry, allowing both the maintenance of food safety criteria for longer periods and the reduction of food waste. Different materials are considered able to exert the required antimicrobial activity, among which are materials containing silver. However, challenges exist in the application of silver to food contact materials due to knowledge gaps in the production of ingredients, stability of delivery systems in food matrices and health risks caused by the same properties which also offer the benefits. Aims of the present study were to test the effectiveness and suitability of two packaging systems, one of which contained silver, for packaging and storing Stracchino cheese, a typical Italian fresh cheese, and to investigate if there was any potential for consumers to be exposed to silver, via migration from the packaging to the cheese. Results did not show any significant difference in the effectiveness of the packaging systems on packaged Stracchino cheese, excluding that the active packaging systems exerted an inhibitory effect on the growth of spoilage microorganisms. Moreover, silver migrated into the cheese matrix throughout the storage time (24 days). Silver levels in cheese finally exceeded the maximum established level for the migration of a non-authorised substance through a functional barrier (Commission Regulation (EC) No. 450/2009). This result poses safety concerns and strongly suggests the need for more research aimed at better characterizing the new packaging materials in terms of their potential impacts on human health and the environment.